The little book about the large universe - Szybka, Sebastian Jan (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2021)
We live in extraordinary times for cosmologists. A vast amount of new astronomical data is pushing our model of the universe to its limits. An interest in cosmology is growing. The Little Book of Cosmology by Lyman Page is a concise up-to-date approachable introduction to the topic.
Keywords: cosmology; universe; cosmos; astronomy; physics; cosmic microwave background; general relativity; background radiation; CMB; WMAP; Albert Einstein